PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA TOKO ALFAMART VL MELATI MAS KOTA TANGERANG SELATAN (PT SUMBER ALFARIA TRIJAYA TBK) - Permana, Ajis; Septiani, Fauziah (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of product quality and price on customer satisfaction at the Alfamart VL store. Melati Mas, South Tangerang City. The research method used is a quantitative descriptive method. The sampling technique used the Slovin formula, so that a sample of 100 respondents was obtained. Meanwhile, the primary data collection technique is through a questionnaire which is processed using the SPSS Version 27 application system. The data analysis method uses validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this research are that product quality has a positive and significant effect on customer satisfaction with a coefficient of determination value of 70.1%, and the hypothesis test obtained tcount > ttable (15.174 > 1.984) or a significance of 0.000 < 0.05. Price has a positive and significant effect on customer satisfaction with a coefficient of determination value of 55.3% and the hypothesis test obtained tcount > ttable (11,000 > 1.984) or a significance of 0.000 < 0.05. Product quality and price simultaneously have a positive and significant effect on Customer Satisfaction with the regression equation Y=4.525 + 0.434X1 + 0.321X2. The coefficient of determination value is 73.7%, while the remaining 26.3% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable or (135.914 > 3.090).